Pengaruh Biaya Operasional Terhadap Pendapatan Operasional (BOPO) Dan Net Interest Margin (NIM) Terhadap Return On Assets (ROA) Pada PT Bank Negara Indonesia Tbk 2012-2021 - Delinda Permatasari; Dijan Mardiati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research was conducted with the aim of determining the effect of operational costs on operating income (BOPO) on return on assets (ROA) at PT Bank Negara Indonesia Tbk, the effect of net interest margin (NIM) on return on assets (ROA) at PT Bank Negara Indonesia Tbk and The Influence of Operational Costs on Operating Income (BOPO) and Net Interest Margin (NIM) on Return on Assets (ROA) at PT Bank Negara Indonesia Tbk. The type of research used in this research is quantitative descriptive. The population used is the financial report of PT Bank BNI and the sample is the financial report of PT Bank BNI which has been audited for the period 2012-2021. The data analysis used is the classic assumption test, linear regression test and hypothesis test. The results of multiple linear regression obtained the equation ROA = 7.163 - 0.091BOPO + 0.382NIM. The research results show that partially BOPO has a significant effect on ROA with a sig value of 0.04 < 0.05 and a tcount value of 9.413 > ttable > 2.364). NIM has a significant effect on ROA with a sig value of 0.009 < 0.05 and a t value of 3.557 > t table 2.364. BOPO and NIM simultaneously influence ROA with a Fcount value of 130.673 > Ftable 4.74 and a significance value of 0.000 < 0.05.